The Effect of Social Norms on Physicians’ Intentions to Use Liver Cancer Screening: A Cross-Sectional Study Using Extended Theory of Planned Behavior - Deng Q; Liu W (Dove Medical Press, 2022)
Qingwen Deng,1,2 Wenbin Liu1 1Department of Health Management, School of Public Health, Fujian Medical University, Fuzhou, 350122, People's Republic of China; 2School of Public Health, Fudan University, Shanghai, 200032, People's Republic of ChinaCorrespondence: Wenbin Liu, Tel +86 13799983766, Email wenbinliu126@126.comBackground: Liver cancer is a globally acknowledged threat to public health, and there is a critical and urgent need to determine factors associated with the use of liver cancer screening and to further promote its use.Purpose: To examine whether the extended theory of planned behavior (TPB) incorporating social norms predicts physicians' intentions to use liver cancer screening and to identify the associated factors quantitatively, using contrast-enhanced ultrasound (CEUS) as an example.Methods: A research framework was established by adding social norms to the TPB, based on which the questionnaire for this study was developed. Through multistage random sampling, a cross-sectional questionnaire survey was conducted among 292 physicians in Fujian and Jiangxi provinces. Due to the multicollinearity problem of the data, ridge regression was applied to determine the influencing factors of physicians' intentions to use CEUS.Results: Most participants (87.30%) reported that they were willing to use liver cancer screening in their clinical practice. The scores of TPB variables were generally higher than those of social norms variables. Ridge regression results indicated that the proposed model was explanatory, which has accounted for 73.5% of the total variance in physicians' intentions. Analyses also illustrated the significant role of TPB variables (attitude and perceived behavioral control) and social norms variables (personal norms, organizational norms, and industrial norms) on physicians' intentions to use CEUS.Conclusion: The study extended the TPB by including the concepts of social norms, which is not only conducive to expanding the knowledge of factors associated with physicians' intentions to use liver cancer screening, but also provides implications for developing strategies to promote the use of certain health services or products, such as playing the role of core members, holding panel meetings, and establishing information push systems.Keywords: social norms, intention, liver cancer, screening, physicians